KARAKTERISTIK CAMPURAN BERASPAL (LASTON) AKIBAT PENGARUH PENGGUNAAN INSTANT POWDER SEBAGAI PENGGANTI FILLER - Safariadi, -; Erwan, H. Komala; Akhmadali, - (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
Asphalt Concrete-Wearing Course (AC-WC) a surface layer which is a flexible pavement construction comprising a mixture of hard asphalt and aggregates, mixed, spread and compacted at temperature. This study used King Kong Instant Powder as a substitute of filler on Laston AC-WC mixture to increase strength on concrete asphalt.The purpose of this research is to get the comparison of laston (AC-WC) characteristics with filler from, King Kong Instant Powder, Tiga Roda portland sement and ash stone and analyzed the effect of the use of King Kong Instant Powder as a filler against the strength of Laston. In this study using variations of asphalt content of 5%, 5.5%, 6%, 6.5% and 7%.This research was conducted in Laboratorium Unit Pengujian Mutu Pembinaan Jasa Konstruksi (UPMPJK) Dinas Pekerjaan Umum Provinsi Kalimantan Barat which is at jalan Khatulistiwa km 6,5 Pontianak. The coarse aggregate used is a crushed stone extracted from a stone crusher, which comes from the Peniraman area. For fine aggregates, the river sand is used from the Kapuas River Pontianak.Laboratory test results obtained as Optimum Asphalt Level (KAO) of 6.75% for Asphalt mixture with Instant Powder Kingkong Filler, Portland Cement and Ash Stone. Result of Analysis with Instant Powder Kingkong Filler At 6.75% KAO obtained Stability value of 1721,7 Kg, Flow 3,8 mm, VIM 4,9%, VFB 72,4%, VMA 20,1% and MQ 454,7 Kg. Result of Analysis with Portland Cement Filler At KAO 6.75% obtained result of 1355,5 Kg, Flow 3,7 mm, VIM 5,3%, VFB 74,0%, VMA 20,5% and MQ 366,8 Kg. Result Analysis with Filler Ash stone at KAO 6.75% got result of 1158,7 Kg, Flow 3,8 mm, VIM 5,9%, VFB 72,9%, VMA 20,6% and MQ 305,7 Kg.The end result shows that in terms of quality, the use of Kingkong Intant Powder as Filler is able to provide good characteristic of Laston, this can be seen from the value of stability, Flow, VMA, VMA, and MQ generated, compared with the use of Porland Cement Filler and Filler Abu Batu. Kingkong Intant Powder can be an alternative to its use as a Filler because the resulting laston characteristics are almost identical to the commonly used filler for portland cement, and stone ash where the resulting values fall within the required specifications. 1. Alumni Prodi Teknik Sipil FT. UNTAN2. Dosen Prodi Teknik Sipil FT. UntanKeywords: Laston (AC-WC)Filler, Instant Powder.